Structural, morphological and thermal properties of kenaf microcrystalline cellulose/poly (butylene adipate-co-terephthalate) films for packaging applications - Aatikah Meraj; Ahmad Safwan Ismail; Mohammad Jawaid (Taylor and Francis, 2025)
The aim of this work is to use microcrystalline cellulose (MCC), obtained from kenaf fibers by using eutectic green solvents, to build compostable packaging films by adding them to Poly (butylene adi- pate-co-terephthalate) (PBAT). In this study, microcrystalline cellulose was incorporated into PBAT composites through melt-mixing, followed by hot pressing at 130°C. PBAT and MCC were produced in various formulations (0.5, 1, 1.5 wt%) to enhance and sustain inherent characteristics of films. The structural, morphological, thermal, and tensile properties of PBAT and microcrystalline cellulose film were examined using X-ray Diffraction, Scanning electron microscope (SEM), Thermal analysis, and Universal Testing Machine. The uniform dispersion of MCC within the PBAT matrix significantly contributes to improved thermal stability, as evidenced by delayed degradation, and enhanced heat resistance. SEM makes it evident that addition of MCC to PBAT influences the surface morphology, with an optimal range promoting mechanical adherence through roughness. However, excessive MCC content leads to imperfections such as cavities, potentially compromising material performance. The inclusion of MCC content enormously raised the tensile modulus of the PBAT/MCC film, increasing its stiffness while tensile strength decreased on addition of MCC in PBAT/MCC formulations. Cellulose film could potentially be used as a biodegradable film in food packaging applications.